2006
DOI: 10.1245/aso.2006.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Diagnosis in Women ≤ 40 versus 50 to 60 Years: Increasing Size and Stage Disparity Compared With Older Women Over Time

Abstract: Since the 1980s, women aged 50 to 60 years have enjoyed a greater decrease in tumor size and percentage with positive nodes. These data could be the result of ineffective screening of younger women or of more aggressive tumor biology. Further study is required to determine whether more effective identification and screening of young, high-risk women can result in earlier detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 30 publications
4
54
1
3
Order By: Relevance
“…The lack of decrease in stage despite detecting smaller tumors in the second period in our study can be related to the high rate of young breast cancer patients and higher rates of lymph node metastases in these patients. Indeed, the axillary lymph node metastasis rate in our series is higher than the National Breast Cancer Database (50%) as well as Western countries (30-40%), and shows a significant decrease in the second period of the study (6,7,13). The rates of lymph node metastasis in young patients during both study periods appear to be significantly higher as compared to patients over 40 years of age.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The lack of decrease in stage despite detecting smaller tumors in the second period in our study can be related to the high rate of young breast cancer patients and higher rates of lymph node metastases in these patients. Indeed, the axillary lymph node metastasis rate in our series is higher than the National Breast Cancer Database (50%) as well as Western countries (30-40%), and shows a significant decrease in the second period of the study (6,7,13). The rates of lymph node metastasis in young patients during both study periods appear to be significantly higher as compared to patients over 40 years of age.…”
Section: Discussioncontrasting
confidence: 53%
“…Early diagnosis enables higher rates of surgical treatment, especially breast conserving surgery, thus yielding more successful treatment outcomes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relative infrequency of the disease in young women, breast cancer is the leading cause of cancer-related death in women aged Յ40 years, and survival rates for young women with breast cancer are lower than those of their older counterparts [4]. Research has repeatedly revealed that younger women are more likely to present with larger sized tumors and a greater number of involved lymph nodes [5,6]. Factors that could contribute to these women pre- …”
Section: Introductionmentioning
confidence: 99%
“…In young women, the current data suggest a greatly reduced breast cancer risk associated with physical activity 36 . The mean age of patients was 36.29 years (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).It is less that than found in 37,38,27 . However, A. KWONG et al and JL.…”
Section: Resultsmentioning
confidence: 96%